Embracing parenting role in childhood obesity - Jiying Ling; Mekdes Gebremariam (BMC, 2023)
Abstract Active parental engagement is crucial in controlling childhood obesity. However, optimal strategies to engage parents and mechanisms linking parents' involvement to childhood obesity prevention need further investigation. In this editorial, we provide a background to invite contributions to the BMC Public Health collection titled 'Parenting role in childhood obesity'.